Developing a systems engineering activity for middle school students using LEGO robotics. - Johnson, Aaron W.; Willner-Giwerc, Sara.; Grogan, Paul T. (Tufts University. Tisch Library., 2017)
Formal education in systems engineering (SE) has grown precipitously in recent decades. SE education emphasizes teamwork and communication skills and takes a broad perspective on engineering to integrate knowledge across multiple disciplines. However, SE academic programs have traditionally focused on master's degrees and continuing education programs. Younger students can also benefit from SE education, as many fundamental SE concepts align with K-12 STEM educational objectives. SE topics provide an interdisciplinary opportunity to design and build while also considering tradeoffs in a collaborative activity, and knowledge of SE is also important for developing students' technological literacy. We have developed an activity to teach SE concepts to middle school students using LEGO EV3 robotics. Students were challenged to design and build a "toxic waste disposal robot." Specifically, this activity sought to accomplish three learning objectives: 1) A system can be decomposed into subsystems, 2) Coordinate activities by communicating requirements and interfaces, and 3) Testing reveals problems and changes often affect others' work. In the first iteration of our activity six students worked together on one robot. Pairs of students each focused on a different subsystem: a manipulator arm, the robot chassis, or the software. While students showed promising SE behaviors, this iteration was unsuccessful on multiple levels. The challenge was too difficult, and it kept students from connecting the SE learning objectives to the activity. In the second iteration of our activity, students were given a pre-built manipulator arm and chassis with software already installed. The focus was on integrating and modifying the two components to complete a series of challenges. This iteration of the activity was much more successful; students were able to complete the challenge in the allotted time, but not without thought and effort. Students also achieved the learning objectives, demonstrating an understanding of SE concepts and how they related to the activity. In this paper we present details of the two iterations of our systems engineering activity and evaluate the successes and challenges of each. By presenting our entire development process we seek to emphasize important considerations for anyone developing a SE activity for K-12 students. We also present an initial qualitative assessment that shows students thinking about the systems engineering learning objectives during full-group discussions.